Implications of irrigation water quality in tropical farms - B. Guerra Tamara; A. Torregroza-Espinosa; D. Pinto Osorio; M. Moreno Pallares; A. Corrales Paternina; A. Echeverría González (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Irrigation system water quality is a complex issue that involves the combined effects of various surface water management parameters. Monitoring of irrigation water quality is essential for the sustainability of crop production and productivity. The department of Sucre, in northern Colombia, is predominantly a ranching and agricultural region where agriculture is the main source for livelihoods. The purpose of this study was to assess the physicochemical quality of surface water in irrigation systems at 141 farms.METHODS: To this end, 141 water samples were taken to determine 22 physicochemical parameters. All in-situ measurements and laboratory analysis were performed using standard methods. The results obtained were compared with the international standards proposed by the United Nations’ Food and Agriculture Organization and the World Health Organization. Salinity and sodicity were measured using the irrigation water classification diagram, and the level of correlation between the 22 variables was assessed by means of correlation analysis.FINDINGS: The results obtained indicate that based on the measured parameters, the water is classified as appropriate for use in irrigation systems. The maximum and minimum pH values were 9.32 and 4.40, respectively; the maximum and minimum values of electrical conductivity were 669 and 19.80 µS/cm respectively; the maximum and minimum values of total dissolved solids were 478 and 11.80 mg/L respectively, and the maximum and minimum values of the sodium adsorption ratio were 1.72 and 0.01 mEq/L, respectively. CONCLUSION: Cation and anion concentrations were within the limits allowed by the Food and Agriculture Organization and the WHO. According to the irrigation water classification diagram, the waters were classified as C1S1 and C2S1, which implies that there are no restrictions for their use in irrigation systems, water type (I) and type (II).